Question
upstudy study bank question image url

\( \{ \frac { [ ( 7 ^ { - 3 } ) ^ { 5 } ] ^ { - 1 } } { ( 7 ^ { 4 } ) \cdot ( 7 - 5 ) } \} \cdot \frac { ( 49 ) ^ { 4 } } { 49 ) ^ { - 5 } } \)

Ask by Campbell Davey. in Colombia
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

La expresión simplificada es \( \frac{7^{29}}{2} \) o aproximadamente \( 1.609953 \times 10^{24} \).

Solution

Calculate the value by following steps: - step0: Calculate: \(\frac{\frac{\left(\left(7^{-3}\right)^{5}\right)^{-1}}{\left(7^{4}\right)\left(7-5\right)}\times 49^{4}}{49^{-5}}\) - step1: Evaluate: \(\frac{\frac{\left(\left(7^{-3}\right)^{5}\right)^{-1}}{7^{4}\left(7-5\right)}\times 49^{4}}{49^{-5}}\) - step2: Multiply by \(a^{-n}:\) \(\frac{\left(\left(7^{-3}\right)^{5}\right)^{-1}}{7^{4}\left(7-5\right)}\times 49^{4}\times 49^{5}\) - step3: Multiply the exponents: \(\frac{\left(7^{-3\times 5}\right)^{-1}}{7^{4}\left(7-5\right)}\times 49^{4}\times 49^{5}\) - step4: Subtract the numbers: \(\frac{\left(7^{-3\times 5}\right)^{-1}}{7^{4}\times 2}\times 49^{4}\times 49^{5}\) - step5: Multiply the numbers: \(\frac{\left(7^{-15}\right)^{-1}}{7^{4}\times 2}\times 49^{4}\times 49^{5}\) - step6: Multiply the exponents: \(\frac{7^{-15\left(-1\right)}}{7^{4}\times 2}\times 49^{4}\times 49^{5}\) - step7: Multiply by \(a^{-n}:\) \(\frac{7^{-15\left(-1\right)}\times 7^{-4}}{2}\times 49^{4}\times 49^{5}\) - step8: Simplify: \(\frac{7^{15}\times 7^{-4}}{2}\times 49^{4}\times 49^{5}\) - step9: Multiply the numbers: \(\frac{7^{11}}{2}\times 49^{4}\times 49^{5}\) - step10: Multiply the terms: \(\frac{7^{11}}{2}\times 49^{4+5}\) - step11: Add the numbers: \(\frac{7^{11}}{2}\times 49^{9}\) - step12: Multiply: \(\frac{7^{11}\times 49^{9}}{2}\) - step13: Multiply: \(\frac{7^{29}}{2}\) Para resolver la expresión dada: \[ \{ \frac { [ ( 7 ^ { - 3 } ) ^ { 5 } ] ^ { - 1 } } { ( 7 ^ { 4 } ) \cdot ( 7 - 5 ) } \} \cdot \frac { ( 49 ) ^ { 4 } } { ( 49 ) ^ { - 5 } } \] Vamos a desglosar cada parte paso a paso. 1. **Simplificación de la primera parte:** - \( (7^{-3})^5 = 7^{-15} \) - Entonces, \( [(7^{-3})^5]^{-1} = (7^{-15})^{-1} = 7^{15} \) 2. **El denominador de la primera fracción:** - \( 7^4 \cdot (7 - 5) = 7^4 \cdot 2 \) 3. **La primera fracción se convierte en:** \[ \frac{7^{15}}{7^4 \cdot 2} = \frac{7^{15}}{2 \cdot 7^4} = \frac{7^{15 - 4}}{2} = \frac{7^{11}}{2} \] 4. **Simplificación de la segunda parte:** - \( (49)^4 = (7^2)^4 = 7^8 \) - \( (49)^{-5} = (7^2)^{-5} = 7^{-10} \) - Entonces, \( \frac{(49)^4}{(49)^{-5}} = \frac{7^8}{7^{-10}} = 7^{8 - (-10)} = 7^{8 + 10} = 7^{18} \) 5. **Multiplicamos ambas partes:** \[ \frac{7^{11}}{2} \cdot 7^{18} = \frac{7^{11 + 18}}{2} = \frac{7^{29}}{2} \] Por lo tanto, la expresión simplificada es: \[ \frac{7^{29}}{2} \] También podemos aproximar este resultado numéricamente: \[ \approx 1.609953 \times 10^{24} \] Así que la respuesta final es: \[ \frac{7^{29}}{2} \quad \text{o} \quad \approx 1.609953 \times 10^{24} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To evaluate the expression \[ \{ \frac { [ ( 7 ^ { - 3 } ) ^ { 5 } ] ^ { - 1 } } { ( 7 ^ { 4 } ) \cdot ( 7 - 5 ) } \} \cdot \frac { ( 49 ) ^ { 4 } } { ( 49 ) ^ { - 5 } } \] we can start by simplifying each piece step-by-step. 1. **Evaluate \((7^{-3})^5\)**: \[ (7^{-3})^5 = 7^{-15} \] Now, applying the negative exponent: \[ [7^{-15}]^{-1} = 7^{15} \] 2. **Evaluate the denominator \((7^4) \cdot (7 - 5)\)**: Since \(7 - 5 = 2\), \[ (7^4) \cdot 2 \] 3. **Thus, the first fraction becomes**: \[ \frac{7^{15}}{2 \cdot 7^4} = \frac{7^{15}}{2 \cdot 7^4} = \frac{7^{15 - 4}}{2} = \frac{7^{11}}{2} \] 4. **Now, simplify the second fraction \(\frac{(49)^4}{(49)^{-5}}\)**: Note that \(49 = 7^2\), so: \[ (49)^4 = (7^2)^4 = 7^8 \] and \[ (49)^{-5} = (7^2)^{-5} = 7^{-10} \] Hence, \[ \frac{(49)^4}{(49)^{-5}} = \frac{7^8}{7^{-10}} = 7^{8 - (-10)} = 7^{8 + 10} = 7^{18} \] 5. **Now, put it all together**: \[ \left(\frac{7^{11}}{2}\right) \cdot 7^{18} = \frac{7^{11 + 18}}{2} = \frac{7^{29}}{2} \] Thus, the final result is: \[ \frac{7^{29}}{2} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy